EVALUATION OF IMPORTANCE OF DRAIN IN ELECTIVE ABDOMINAL SURGERIES - Bhattacharjee, Anurag; Ramteke, Harshal (International Journal of Psychosocial Rehabilitation, 2020)
Drains are used in surgery for many years to prevent the accumulation of bodily fluids and improving body function. Drain helps in providing an opening for body fluids, pusflakes, blood or debrided materials that obstructs with wound granulation or provides a source for bacterial infection. Abdominal drainage is performed via usage of pvc or hollow rubber tubes with small openings in the apex point. Placement of a drain via a puncture around the surgical site or abdomen with deep pockets where there the chances of fluid accumulation is at its greatest. this study was to focus the usefulness of the precautionary drainage of peritoneum after abdominal surgeries and to study the duration, the quantity and character of drain and associated various postoperative complications associated with drains, it’s complications and comorbidities. To study the outcome in abdominal surgeries by comparing “drain” and “non-drain” group. All the abdominal surgery cases of both sexes admitted in surgical ward through OPD basis requiring elective abdominal surgeries for various abdominal pathologies will be evaluated with detailed history. Drain use may lead to similar wound infections ,need for additional open procedures for postoperative complications and quality of life scores versus when compared with no drain use. Use of prophylactic drain in abdominal surgeries shows no advantage in helping in reduction of postoperative complications or any other surgical benefit for the same.